Predator vs prey - McMann, Lisa (McMann, Lisa. Going wild, 2017)
Charlie Wilde's dad has been abducted by masked figures who might not even be completely human. And it will take more than her incredible bracelet--which gives her powers from the animal kingdom--to rescue him. Luckily, Charlie's friends now have bracelets of their own with all-new abilities...they just have to work through a few issues first. Maria's device has hair-raising side effects. Mac can't wait to hack into his. And their frenemy, Kelly, swears hers is a dud. If Charlie is going to have any hope of saving her dad--and the world--from their beastly foes, she'll have to help her friends master their powers and come together as a team.